Multifaceted Actions of GFI1 and GFI1B in Hematopoietic Stem Cell Self-Renewal and Lineage Commitment - Beauchemin, Hugues; Möröy, Tarik (Frontiers in Genetics, 2020)
Growth factor independence 1 (GFI1) and the closely related protein GFI1B are small nuclear proteins that act as DNA binding transcriptional repressors. Both recognize the same consensus DNA binding motif via their C-terminal zinc finger domains and regulate the expression of their target genes by recruiting chromatin modifiers such as histone deacetylases (HDACs) and demethylases (LSD1) through an N-terminal SNAG domain that comprises only 20 amino acids. The only region that is different between both proteins is the region that separates the zinc finger domains and the SNAG domain. Both proteins are co-expressed in hematopoietic stem cells (HSCs) and to some extent in multipotent progenitors (MPPS), but expression is specified as soon as early progenitors show signs of lineage bias. While expression of GFI1 is maintained in LMPPs (lymphoid primed multipotent progenitors) that have the potential to differentiate into both myeloid and lymphoid cells, GFI1B expression is no longer detectable in these cells. By contrast, GFI1 expression is lost in megakaryocyte precursors (MKPs) and in megakaryocytic erythrocyte progenitors (MEPs), which maintain a high level of GFI1B expression. Consequently, GFI1 drives myeloid and lymphoid differentiation and GFI1B the development of megakaryocytes, platelets and erythrocytes. How such complementary cell type- and lineage specific functions of GFI1 and GFI1B are maintained is still an unresolved question in particular since they share an almost identical structure and very similar biochemical functions. The cell type specific accessibility of GFI1/B binding sites may offer an explanation, but also the fact that both proteins can have different, non-transcriptional functions where GFI1 controls the activity of DNA repair proteins and GFI1B regulates the Wnt/beta catenin signaling pathway. In addition, GFI1 and GFI1B are required for endothelial cells to become the first blood cells during early murine development and are among those transcription factors needed to convert adult endothelial cells or fibroblasts into hematopoietic stem cells. This role of GFI1 and GFI1B bears high significance for the ongoing effort to generate hematopoietic stem and -progenitor cells de novo for the autologous treatment of blood disorders such as leukemia and lymphoma.